2001
DOI: 10.1093/nar/29.8.e41
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the performance of cDNA microarrays for detecting changes in global mRNA expression

Abstract: The cDNA microarray is one technological approach that has the potential to accurately measure changes in global mRNA expression levels. We report an assessment of an optimized cDNA microarray platform to generate accurate, precise and reliable data consistent with the objective of using microarrays as an acquisition platform to populate gene expression databases. The study design consisted of two independent evaluations with 70 arrays from two different manufactured lots and used three human tissue sources as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(204 citation statements)
references
References 14 publications
8
193
2
1
Order By: Relevance
“…This array contains 638 sequence-verified genes selected from rat cDNA clones (Research Genetics, AL) and the 15K NIA mouse cDNA gene set [52] on the basis of our previous studies [28,37]. It was shown that cross-species hybridization (i.e., mouse clones against rat target samples) using a cDNA platform is accurate and specific [59]. Cells containing the cDNA clones of interest were grown overnight, and 10 Al of the culture medium plus 90 Al of water were incubated at 95 8C for 10 min to release plasmid DNA.…”
Section: Total Rna Isolation and Amplificationmentioning
confidence: 99%
“…This array contains 638 sequence-verified genes selected from rat cDNA clones (Research Genetics, AL) and the 15K NIA mouse cDNA gene set [52] on the basis of our previous studies [28,37]. It was shown that cross-species hybridization (i.e., mouse clones against rat target samples) using a cDNA platform is accurate and specific [59]. Cells containing the cDNA clones of interest were grown overnight, and 10 Al of the culture medium plus 90 Al of water were incubated at 95 8C for 10 min to release plasmid DNA.…”
Section: Total Rna Isolation and Amplificationmentioning
confidence: 99%
“…The mean (range) yield of aRNA for PC3 and PC3-M cells was 3.0 mg (1.8-4.0 mg) and 3.1 mg (1.9-4.8 mg), respectively, Table 1. To evaluate the effect of operator experience, aRNA yields from reactions performed early in the 3-month period (reactions 1-6) were compared to those performed late (7)(8)(9)(10)(11)(12), for both PC3 and PC3-M cells. For PC3 cells, mean yields for early and late reactions were 2.9 and 3.0, respectively, whereas for PC3-M cells, they were 3.1 and 3.1, respectively.…”
Section: Rna Amplificationmentioning
confidence: 99%
“…[3][4][5][6] Standard protocols require B5 mg of total RNA per sample as starting material for high-density oligonucleotide microarrays; B20 mg is required for cDNA-based microarrays. 7,8 Whereas microgram quantities of RNA are readily extracted from whole biopsy specimens, individual specimens consist of a heterogeneous mixture of cell types. This, in turn, imposes practical limitations upon interpretation of resultant array data, particularly when one seeks to identify changes in a single-cell type, as is typically the case.…”
Section: Introductionmentioning
confidence: 99%
“…This software generates significant differences between gene expressions where, a two-fold difference is equal to a P-value of 0.05. [14][15][16][17] All differential expression values were log transformed and balanced, essentially as previously described. 17 Briefly, the differential values were calculated only if the signal to background ratio exceeded 2.0, the signal intensity was above 200 U in at least one of the two channels, and the element diameter exceeded 40% of the mean element diameter for the array.…”
Section: Rna Extractionmentioning
confidence: 99%